Hubungan Interaksi Teman Sebaya Dengan Perilaku Konsumtif Pada Remaja Di SMAN 2 Ngawi - Kristiyanti, Lussi; , Wisnu Sri Hertinjung, S.Psi, M.Psi, Psi (2017)
Adolescence is a period of life that is full of dynamism for the future developments and changes occurred very rapidly in adolescents with a group of peer interaction.he purpose of this study was to determine the relationship of peer interaction with the consumer behavior in adolescents in SMAN 2 Ngawi.Peer interaction affects teenagers behave consumptive. The method used is correlational studies. Subjects in this study were high school students of class X in Ngawi as many as 80 students aged 15-18 years and was taken by multi cluster random sampling. Measuring instruments used is the scale of peer interaction with the consumer behavior. Analysis method performed using analysis of product moment with Statistical product and service solution (SPSS) 16.0 for Windows program. The hypothesis proposed that there is a positive relationship between peer interaction with the consumer behavior in adolescents. The results were obtained rxy of 0.545; p = 0.000 (p <0.01). This means that there is a positive relationship between peer interaction with the consumer behavior in adolescents in SMAN 2 Ngawi. Variable consumer behavior had a mean empirical (RE) = 60.33 and the mean hypothetical (RH) = 55, and the variable ineraksi peers had a mean empirical (RE) = 70.50 and the mean hypothetical (RH) = 67.5. The effective contribution of the variable peer interaction with the consumer behavior adolescent sebasar remaining 29.7% 70.3% There are other factors that influence consumer behavior.